System-level modeling methodology for capturing the pile cap, helical pile group, and soil interaction under uplift loads. (1st October 2020) - Sharma, Anish; Guner, Serhan
Highlights: A well-defined 3D methodology to model soil-structure interaction. Proposed methodology is independent of the computer program used. Tensile uplift load behavior is captured. A comprehensive experimental verification study is presented. Experimental calibration data for 24 specimens is provided. Discrete modeling methods significantly underestimate the system capacity in weaker soils. Abstract: In tall and light structures, such as transmission towers, wind turbines, and light-gauge steel structures, there is an increasing application of pile cap with helical pile foundation systems to resist the uplift loads due to the effects of windstorms and earthquakes. There is a lack of knowledge, published literature, or analysis methods to account for the effects of the pile cap, helical pile group, and soil interactions on the holistic response of the foundations, particularly, for the load conditions creating net uplift loads. In the lack of such, discrete modeling approaches are frequently employed in practice. These approaches isolate each system component and analyze them individually, neglecting the interactions between them. In an attempt to bridge this knowledge gap, this study proposes a system-level modeling methodology for the holistic analysis of pile cap systems in dry soil and static load conditions, while accounting for the effects of interactions between system components and the inherent material nonlinearities. The methodology employs a three-stage process in which the material and interaction properties are calibrated with the experimental benchmark specimens. The failure mechanisms are also experimentally verified based on the relative displacement of the piles. Important modeling considerations are discussed, and experimental benchmark specimens are provided to assist practitioners in accurately performing system-level analyses. The effectiveness of the proposed methodology is discussed, and the responses obtained, including the load–displacement responses, load capacities, and failure modes, are compared with those obtained from the discrete modeling approaches. The results demonstrate that discrete modeling approaches significantly underestimate the load capacity while not accurately predicting the governing behavior and the failure modes.